Sense of external agency is sustained by multisensory functional integration in the somatosensory cortex. Issue 14 (15th July 2020) - Piras, Federica; Vecchio, Daniela; Ciullo, Valentina; Gili, Tommaso; Banaj, Nerisa; Piras, Fabrizio; Spalletta, Gianfranco
Abstract: "Sense of agency" (SoA), the feeling of control for events caused by one's own actions, is deceived by visuomotor incongruence. Sensorimotor networks are implicated in SoA, however little evidence exists on brain functionality during agency processing. Concurrently, it has been suggested that the brain's intrinsic resting‐state (rs) activity has a preliminary influence on processing of agency cues. Here, we investigated the relation between performance in an agency attribution task and functional interactions among brain regions as derived by network analysis of rs functional magnetic resonance imaging. The action‐effect delay was adaptively increased (range 90–1, 620 ms) and behavioral measures correlated to indices of cognitive processes and appraised self‐concepts. They were then regressed on local metrics of rs brain functional connectivity as to isolate the core areas enabling self‐agency. Across subjects, the time window for self‐agency was 90–625 ms, while the action‐effect integration was impacted by self‐evaluated personality traits. Neurally, the brain intrinsic organization sustaining consistency in self‐agency attribution was characterized by high connectiveness in the secondary visual cortex, and regional segregation in the primary somatosensory area. Decreased connectiveness in the secondary visual area, regional segregation in the superior parietal lobule, and information control within a primary visual cortex‐frontal eye fields network sustained self‐agency over long‐delayed effects. We thus demonstrate that self‐agency is grounded on the intrinsic mode of brain function designed to organize information for visuomotor integration. Our observation is relevant for current models of psychopathology in clinical conditions in which both rs activity and sense of agency are altered. Abstract : We investigated the relation between agency and functional interactions among brain regions using network analysis. Self‐agency is grounded on the intrinsic mode of brain function designed to organize information for visuomotor integration. This is relevant for current models of psychopathology in clinical conditions in which both brain functional activity and sense of agency are altered.